Aerobic Epoxidation of Olefins Catalyzed by the Cobalt-Based Metal-Organic Framework STA-12(Co) - Beier, Matthias J.; Kleist, Wolfgang; Wharmby, Michael T.; Kissner, Reinhard; Kimmerle, Bertram; Wright, Paul A.; Grunwaldt, Jan-Dierk; Baiker, Alfons (Chemistry : a European journal, 2012)
A Co‐based metal–organic framework (MOF) was investigated as a catalytic material in the aerobic epoxidation of olefins in DMF and exhibited, based on catalyst mass, a remarkably high catalytic activity compared with the Co‐doped zeolite catalysts that are typically used in this reaction. The structure of STA‐12(Co) is similar to that of STA‐12(Ni), as shown by XRD Rietveld refinement and is stable up to 270 °C. For the epoxidation reaction, significantly different selectivities were obtained depending on the substrate. Although styrene was epoxidized with low selectivity due to oligomerization, (E)‐stilbene was converted with high selectivities between 80 and 90 %. Leaching of Co was low and the reaction was found to proceed mainly heterogeneously. The catalyst was reusable with only a small loss of activity. The catalytic epoxidation of stilbene with the MOF featured an induction period, which was, interestingly, considerably reduced by styrene/stilbene co‐epoxidation. This could be traced back to the formation of benzaldehyde promoting the reaction. Detailed parameter and catalytic studies, including in situ EPR and EXAFS spectroscopy, were performed to obtain an initial insight into the reaction mechanism. Aim for the STAs: The metal–organic framework catalyst STA‐12(Co) showed remarkable activity in the aerobic epoxidation of E‐stilbene in DMF (see figure) and could be efficiently recycled. High selectivity (80–90 %) for stilbene oxide was observed. The induction period of the reaction could be reduced by styrene/stilbene co‐epoxidation. Detailed parameter studies combined with spectroscopic investigations were performed to obtain an initial insight into the reaction mechanism.